Treelands or Grasslands in the Rajputana Desert? - Satyanarayan, Y. (Indian Forester, 1958)
There are no two opinions regarding the need or urgency for the reclamation of the Rajasthan Desert. The principle of afforestation has been accepted by the ad hoc committee and others. But treelands will not solve all the problems, as stated by Shah. The chief problems in the reclamation of the desert are ( 1) immobilization of sands, (2) restoration of original vegetation by means of plant succession, and ( 3) provision of fodder for the sheep industry, which is the largest in India. These latter facts appear to have been ignored by earlier workers. Any attempt to establish treelands under the existing environmental conditions should be tried out with caution. Experiments so far have shown that such attempts are costly. Establishment of grasslands as pioneering vegetation on the dunes and sand plains should be attempted first. There are many indigenous grasses and legumes in the arid zone which form dense associations and can be readily utilized for immobilizing the sand dunes, increasing soil fertility, providing fodder for sheep, cattle and camels in season and hay for winter-feeding. Being pioneer vegetation they would pave the way for an ecological succession of other species, progressing towards the climax. It is however, not argued that treelands have no place in such a grassland management. Without trees, permanent reclamation is not possible and hardy, drought resistant trees should be established either simultaneously with reseeding or after the stabilization of the dunes. New principles of grassland management should be introduced.